The Outcome of Vaginal Birth After Caesarean Section (VBAC): A Descriptive Study (Medicine Today, 2013)
The study, conducted in the tertiary care hospital of Dhaka Bangladesh, describes the outcome of vaginal birth after caesarean section (VBAC) in women with a previous caesarean. A prospective study was carried out from 1st January 2007 to 31st December, 2007 on 126 women with one prior lower segment cesarean section (LSCS) for a nonrecurrent cause. All unbooked women and those with estimated fetal weight more than 3.5 kg, breech presentation, history of postoperative wound infection after previous LSCS, anemia (Hb < 10 gm%), pregnancy induced hypertension, diabetes, heart disease, renal disease, cephalopevic disproportion abnormal presentation and placenta praevia were excluded from the study. An informed consent was taken for allowing a trial of vaginal delivery. Spontaneous onset of labor was awaited up to 41 weeks. Induction of labor was considered only in highly selected cases. Labor was constantly supervised by competent staff and meticulously monitored by cardiotocography (CTG). Out of the 126 women enrolled for the study, 26 had to leave the station leaving a total of 100 patients; 72 patients underwent elective repeat C/S, 28 patients (28%) of these underwent trial of labour, among them 15 had successful vaginal delivery (53.57) but 13 patients failed the attempt and had to undergo emergency caesarean section. To assist in the 2nd stage of labour, 6 had ventouse application. In total 85 cases needed repeat caesarean section. Among the cases there was one case of scar dehiscence (6.6%), one case of cervical tear (6.6%), two cases of manual removal of placenta (13.3%), one case of post partum hemorrhage (6.6) and one case of puerperal pyrexia (6.6).Perinatal morbidity was comparable with the elective repeat C/S group. VBAC should be considered in cases of previous one cesarean delivery for nonrecurrent indication. DOI: http://dx.doi.org/10.3329/medtoday.v25i1.15902 Medicine Today 2013 Vol.25(1): 14-17